Heterologous expression and mutagenesis of recombinant Vespa affinis hyaluronidase protein (rVesA2) - Rungsa,Prapenpuksiri (2019)
Abstract Background: Crude venom of the banded tiger waspVespa affinis contains a variety of enzymes including hyaluronidases, commonly known as spreading factors. Methods: The cDNA cloning, sequence analysis and structural modelling of V. affinis venom hyaluronidase (VesA2) were herein described. Moreover, heterologous expression and mutagenesis of rVesA2 were performed. Results: V. affinis venom hyaluronidase full sequence is composed of 331 amino acids, with four predicted N-glycosylation sites. It was classified into the glycoside hydrolase family 56. The homology modelling exhibited a central core (α/β)7 composed of Asp107 and Glu109, acting as the catalytic residues. The recombinant protein was successfully expressed in E. coli with hyaluronidase activity. A recombinant mutant type with the double point mutation, Asp107Asn and Glu109Gln, completely lost this activity. The hyaluronidase from crude venom exhibited activity from pH 2 to 7. The recombinant wild type showed its maximal activity at pH 2 but decreased rapidly to nearly zero at pH 3 and was completely lost at pH 4. Conclusion: The recombinant wild-type protein showed its maximal activity at pH 2, more acidic pH than that found in the crude venom. The glycosylation was predicted to be responsible for the pH optimum and thermal stability of the enzymes activity.